Repellent activity of selected essential oils against Aedes aegypti - Choochote W. (2014)
Essential oils extracted from ten plant species were screened for repellency against Aedes aegypti mosquitoes. Three oils; Zanthoxylum piperitum, Anethum graveolens and Kaempferia galanga, exerted protection against A. aegypti, with median complete-protection times of 1, 0.5 and 0.25 h, respectively. The protection times were increased significantly by incorporating 10% vanillin. The highest potential was established from Z. piperitum oil + 10% vanillin (2.5 h, range = 1-2.5 h). Mixtures from pairs of the effective oils possessed slight repellency that ranged from 0-0.5 h. None of the oil combinations repelled A. aegypti for longer than their constituent oil alone. With vanillin added, however, each oil mixture provided improved protection, which was approximately equal to oil on its own. GC/MS analysis revealed that the main component of Z. piperitum fruit oil was limonene (37.99%), with minor amounts of sabinene (13.30%) and β-myrcene (7.17%). Repellent testing of stored samples of Z. piperitum fruit oil against A. aegypti demonstrated that repellent activity of those kept at - 20 °C or 4 °C was present for a period of at least 3 months. Therefore, the essential oil of Z. piperitum fruit may prove useful in the development of mosquito repellents as an effective personal protection measure against mosquito bites. © 2007.